Designing 2d Animation Illustration Assets to Raise Environmental Awareness in the Wonorejo Mangrove Forest - Sheila Shartika; Hendro Aryanto (Universitas Negeri Surabaya, 2025)
The Wonorejo Mangrove Forest is currently facing environmental pollution caused by plastic waste, which threatens the balance of its ecosystem. One of the main contributing factors is the lack of environmental awareness, especially among children. This study aims to design 2D animation illustration assets as an educational medium to raise environmental awareness from an early age. The research uses a qualitative approach, with data collected through interviews, observations, internet sources, and documentation. The design concept includes storyline development, themes, characters, and storyboards to support engaging and innovative educational animation. Supporting media such as posters, stickers, pins, and keychains are also included. The results of this design are expected to serve as an effective educational tool to encourage the preservation of the Mangrove Forest